Transforming the online learning space through advanced development retreats - Belton , Daniel J.; Folley , Sue; McGown , Sophie (Research in Learning Technology, 2021)
Learning technologies have the potential to transform Higher Education, although multifaceted demands on staff time, confidence and training in using new technologies, and a lack of support can make this transformation difficult. The University of Huddersfield recently transitioned to a new virtual learning environment (VLE), which provided the opportunity to change the way staff view and use the new VLE for teaching and learning. As part of this project, three off-site retreats were run to help staff to reflect on and develop their teaching practice to better support student learning in the digital space and develop advanced online resources that support the democratisation of learning, close differential attainment gaps and give every student the best chance of success. Although much is written about different models of practice, there is a lack of theory and conceptualisation around changing practice. Examining the motivations and experiences of staff who participated provides insight into the challenges of implementing change on an institutional level, whilst examining their setup and design highlights ways to support staff during this process. Using participant feedback and experiences to underpin this research, we explore the immediate and ongoing outcomes of these off-site retreats to help transform the University’s approach to technology-enhanced learning.